Hearing learner voice in health promoting schools through participatory action research - Sonn, Brenda; Santens, Anneleen; Ravau, Sarah (Faculty of Education, University of the Free State, 2011)
The participation of learners in school life and learner voice is important for learner development and the implementation of school interventions. In this paper we argue that learner participation and learner voice in school-community interventions contribute to learners’ development of a critical consciousness and to their understanding of themselves in society. We show how participatory action research methodologies such as reflective writing, metaphor, and photovoice supported 30 secondary school learners from schools in challenging contexts to explore and extend themselves as participants in Health Promoting Schools. The creative design of these participatory action research methods and the discursive spaces which these methods provided gave learners the opportunity for self-expression and deepened their understanding of complex social issues such as diversity, drug abuse, gangsterism and violence, and how they are affected by these issues.
Keywords: Participatory action research; Participatory methodologies; Health promoting schools; Learner voice; Diversity; Substance abuse; Violence